Sosialisasi Strategi Membaca Metakognitif Kepada Siswa SMAN 1 Kefamenanu Nusa Tenggara Timur - Yulita, Delti; Sinu, Gloriana (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
The purpose of this program is to improve students’ ability in reading English text by exposing the metacognitive reading strategy to make them an effective reader. This program was conducted in Senior High School in Kefamenanu, East Nusa Tenggara where the preliminary research has shown that students’ reading ability is still low. The method used in this service program is introducting the significance benefits of metacognitive in reading, exploring what category in metacognitive that used frequently by the students, and applying the metacognitive strategy in reading English text. Based on the first survey, the students did not familiar with metacognitive strategy in reading. After being introducing to metacognitive reading strategy, students become more aware about the importance of using strategy in reading. The result of metacognitive questionnaire showed that students frequently use support strategy more than problem-solving and global strategy. At last, students’ give positive feedback and perception about metacognitive reading strategy.